Focal white matter lesions drive grey matter inflammation and synapse loss - Omar de Faria; Stavros Vagionitis; Andrea Lopez-Lopez; Michael Perry; Joseph Jo Yin Wong; Leslie Rodríguez-Kirby; Bastien Hervé; Balazs Viktor Varga; Eneritz Agirre; Sabrina Ghosh; Sebastian Timmler; Mert Yucel; et al. (Nature, 2026)
Abstract Focal white matter lesions occur in most neurodegenerative disorders 1–3 . Despite occurring early in disease, white matter lesions are considered to be independent of, or secondary to, grey matter neuroinflammation, synapse loss and altered neuronal activity 4–7 . Notably, their functional effect on neuronal circuits remains understudied. To address this, we generated a focal white matter lesion in the rat brain within a clinically relevant, anatomically well-defined circuit, in which these lesions occur in many neurodegenerative disorders 8–10 . Here we show that focal white matter lesions evoke transient neuronal activity changes and microgliosis, with subsequent synapse loss and increased microglial engulfment in the grey matter, which is reversed if myelin regeneration completes. Grey matter microgliosis is often considered to be detrimental; however, we show that it is an integral part of regeneration and is conserved across three distinct mouse circuits and lesioning methods. Preventing these transient changes in the grey matter blocks myelin regeneration in the white matter. Conversely, inducing myelin regeneration failure leads to chronic grey matter neuroinflammation. This recapitulates the low-grade inflammation considered to be a dominant mechanism underlying neurodegeneration 7,11,12 . Our findings reveal a form of regenerative plasticity coupling white matter integrity to grey matter function, which may underlie multiple neurodegenerative conditions, and highlight the potential of targeting myelin regeneration to prevent chronic neuroinflammation.